Aggressive giant cystic lymphatic malformation in a newborn - Çalış, Mert; Konaş, Ersoy; Takcı, Şahin; Yurdakök, Murat; Tunçbilek, Gökhan (The Turkish Journal of Pediatrics, 2013)
Lymphatic malformations are uncommon, benign and congenital malformations of the lymphatic system exhibiting lack of development of communication between the lymphatic and venous circulation. We report the unusual case of rapidly expanding giant lymphatic malformation of the torso, bilateral axillae and left upper extremity of a newborn. As the first-line treatment, aspiration and sclerotherapy with bleomycin were performed. The sclerotherapy failed to cause regression of the mass, and rapid expansion of the malformation necessitated surgery. Partial resection of the mass was performed. Clinical symptoms of respiratory distress resolved in the early postoperative period, and the patient became hemodynamically stable. However, intrathoracic invasion of the mass developed, leading to restriction of thoracic expansion, ending in death. In conclusion, surgical treatment of giant lymphatic malformations remains challenging.